2014
DOI: 10.1186/s40555-014-0056-9
|View full text |Cite
|
Sign up to set email alerts
|

Tidal variation in fish assemblages and trophic structures in tropical Indo-Pacific seagrass beds

Abstract: Background: Tidal cycle is an important factor which regularly changes coastal fish assemblages in shallow waters. However, the variations in fish assemblage and trophic structure across tidal cycles in tropical seagrass beds are rarely discussed. We used underwater visual censuses to quantify fish abundance and diversity from the shallow intertidal to the subtidal zone during both flood and ebb tides in seagrass beds surrounding the Dongsha Island, South China Sea. We also recorded fish feeding habits by anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 49 publications
(67 reference statements)
1
16
0
Order By: Relevance
“…The shallow northern waters (depth: 1-3 m) of Dongsha Island are often calm and clear and covered with high seagrass coverage (covering approximately 80-90% of the study area). Previous studies [30,31] showed a high abundance of reef fish, seagrass, and coral in the northern waters of Dongsha. Seagrass species in the canopies are mainly mixtures of Thalassia hemprichii, Cymodocea rotundata and Cymodocea serrulata.…”
Section: Study Sitementioning
confidence: 89%
See 3 more Smart Citations
“…The shallow northern waters (depth: 1-3 m) of Dongsha Island are often calm and clear and covered with high seagrass coverage (covering approximately 80-90% of the study area). Previous studies [30,31] showed a high abundance of reef fish, seagrass, and coral in the northern waters of Dongsha. Seagrass species in the canopies are mainly mixtures of Thalassia hemprichii, Cymodocea rotundata and Cymodocea serrulata.…”
Section: Study Sitementioning
confidence: 89%
“…In total, eight surveys were conducted bimonthly only during the warm season (from April to October) in 2010 and 2011 to avoid intense northeastern monsoons during the cool season and coincide with the main recruitment season for reef fishes at Dongsha Island [30]. The surveys were conducted using six 20 × 2 m replicated transects that had been placed at one of six haphazardly chosen locations in each of the four habitat types (Figure 1c).…”
Section: Study Sitementioning
confidence: 99%
See 2 more Smart Citations
“…In this case, the group of fish is the most dominant carnivores on seagrass beds in the study areas. Similarly, the group of fish carnivores contributed about 70% of the total fish abundance in seagrass beds at Donghsa Island's (Lee et al, 2014), but there was differences, the group of fish carnivores (20%) and herbivores (20%) in the Formoso River estuaryPernambuco, Brazil (Pereira et al, 2010). Besides that, (Appendix 6) showed that seagrass provides a diversity of fish food on seagrass in the study area.…”
Section: The Abundance and Diversity Of Fish As Indicators Of Seagrasmentioning
confidence: 86%